SEBUAH PENELITIAN MENGENAI KEMAMPUAN SISWA KELAS 1 SMAN 3 PEKANBARU DALAM MENULIS TEKS PROSEDUR - Bhakti Fajar; Erni '; M.Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This descriptive research was aimed to find out the ability of the first year students of SMAN 3Pekanbaru in writing procedure texts. The research data were collected in September 2016. The subject of this research was class X IPA 4 which consisted of 32 students. The data were collected by giving a writing test to the students.Based on the research, it was found out that first: the ability of the first year students in writing procedure texts is in good level with the mean score of 63.00. Second, the students’ mean score in terms of grammar is in moderate level with the mean score of 49.17, in terms of organization is in good level with the mean score of 78.75, in terms of mechanic is in good level with the mean score of 61.45, in terms of vocabulary is in moderate level with the mean score of 48.33, in terms of fluency is in good level with the mean score of79.37. As a conclusion, the highest score obtained by the students is in terms of fluency with the mean score of 79.37 which is categorized into good level, and the lowest score that the students got is in terms of vocabulary the mean score of 48.33 which is categorized into moderate level. English teacher may develop the students’ motivation and encourage them to learn more about procedure texts as a practice of writing procedure texts in order to make the students familiar with writing materials. For next researcher, the writer suggests that to conduct other research in this school.